TREATMENT OF SCABIES ACCOMPANIED BY BACTERIAL PNEUMONIA IN MIX CAT - Lola Yolanda Br Barus; Putu Ayu Sisyawati Putriningsih; I Nyoman Suartha (Buletin Veteriner Udayana, 2025)
Scabies is a dermatological condition caused by the parasitic mite Sarcoptes scabiei. Infection with Sarcoptes scabiei induces severe pruritus, which can lead to alopecia and skin lesions. This disease is often accompanied by secondary infections, as the compromised immune response in affected individuals increases their susceptibility to opportunistic pathogens. Prompt and appropriate treatment is therefore essential to ensure a favorable prognosis. A 2.5-year-old mixed-breed female cat named Mimi, weighing 2.3 kg, presented with clinical signs of pruritus, sneezing, and nasal discharge from both nostrils, persisting for one month prior to examination. A physical examination revealed alopecia on the ear and neck regions, crusting on the ears and frontal area, mucous nasal discharge, and pale oral mucosa. Deep skin scraping of the alopecic and crusted areas identified the presence of Sarcoptes scabiei mites. Further radiographic evaluation revealed an alveolar pattern in the lungs. Additionally, microbiological analysis of the nasal discharge confirmed the presence of Streptococcus sp. A complete blood count indicated leukocytosis, lymphocytosis, and granulocytosis. Based on these findings, the cat was diagnosed with scabies complicated by bacterial pneumonia, with a favorable prognosis. The treatment regimen included scabies therapy with an ivermectin injection at a dose of 0.03 mL and diphenhydramine HCl at a dose of 0.3 mL, both administered subcutaneously. Antibiotic therapy consisted of amoxicillin combined with clavulanic acid (25 mg formulation), dosed at 62.5 mg (1 mL) per administration, given orally twice daily for 10 days. Anti-inflammatory treatment included methylprednisolone (4 mg formulation), dosed at 2 mg per 2–6 kg body weight, administered orally once daily for seven days. Supportive therapy comprised Sangobion syrup and fish oil to promote erythropoiesis and enhance hair regrowth. After seven days of treatment, the nasal discharge was absent, and sneezing episodes were significantly reduced. Progressive hair regrowth and weight gain were observed, with marked improvement continuing up to day 100.